Loss of Nup155 promotes high fructose-driven podocyte senescence by inhibiting INO80 mRNA nuclear export - Li Chen; Tangdi Xu; Zixuan Wang; Chengzhi Wang; Lei Fang; Lingdong Kong (Journal of Advanced Research)
Introduction: Podocyte senescence causes podocyte loss and glomerulopathy. Excessive fructose intake is a risk factor for podocyte injury. However, whether high fructose promotes podocyte senescence remains unknown. Objectives: To explore the pathological mechanism by which high fructose drives podocyte senescence and find natural compounds to alleviate podocyte senescence. Methods: Podocyte senescence was characterized with senescence-associated beta-galactosidase (SA-β-gal) staining, Western blot, real-time quantitative polymerase chain reaction (qRT-PCR), comet assay and immunofluorescence. Proteomics analysis was performed to identify differentially expressed proteins in high fructose-exposed podocytes. Podocyte nuclear pore complexes (NPCs) and foot processes were observed by transmission electron microscopy. The mRNA and protein levels of nucleoporin 155 (Nup155) and inositol requiring mutant 80 (INO80) were detected by qRT-PCR, Western blot and immunofluorescence. Virtual screening was conducted to find natural compounds that target Nup155. Results: High fructose increased SA-β-gal activity, protein level of p53, p21, p16 and phosphorylated histone H2AX (γ-H2AX), as well as mRNA expression of interleukin-1β (IL-1β), IL-6 and tumor necrosis factor α (TNF-α) in rat glomeruli and podocytes. Proteomic analysis unraveled a crucial molecule Nup155, which was decreased in high fructose-induced podocyte senescence. Meanwhile, the number of podocyte NPCs was also decreased in vivo and in vitro. Consistently, high fructose suppressed nuclear export of INO80 mRNA, thereby down-regulated INO80 protein expression in podocyte senescence. Deletion of Nup155 inhibited INO80 mRNA nuclear export to induce podocyte senescence, whereas overexpression of Nup155 or INO80 alleviated high fructose-induced podocyte senescence. Ferulic acid was found to up-regulate Nup155 by both direct binding to stabilize Nup155 protein and enhancing its transcription, to promote INO80 mRNA nuclear export in the mitigation of high fructose-caused podocyte senescence. Conclusion: High fructose induces podocyte senescence by decreasing Nup155 to inhibit INO80 mRNA nuclear export. Ferulic acid targeting Nup155 may be a potential strategy to prevent high fructose-induced podocyte senescence.